2005
DOI: 10.1007/s00520-005-0894-4
|View full text |Cite
|
Sign up to set email alerts
|

Medium-term effects of chemotherapy in older cancer patients

Abstract: The results suggest that chemotherapy has no negative effects on cognitive functions after the first six months following the onset of treatment. It was demonstrated that complete recovery of cognitive functions is independent of the patient's age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 25 publications
(27 reference statements)
0
5
0
4
Order By: Relevance
“…All the other cognitive studies which have measured psychological distress have found no correlation between objective cognitive performance and depression, anxiety and/or mood [11,[13][14][15][16][17]76,78,79,84,85,87,91,119,147]. However, as discussed in Section 6, many studies have found a strong association between perceived cognitive impairment and anxiety and/or depression [11,17,78,87,91,101].…”
Section: Anxiety Depression and Stressmentioning
confidence: 91%
“…All the other cognitive studies which have measured psychological distress have found no correlation between objective cognitive performance and depression, anxiety and/or mood [11,[13][14][15][16][17]76,78,79,84,85,87,91,119,147]. However, as discussed in Section 6, many studies have found a strong association between perceived cognitive impairment and anxiety and/or depression [11,17,78,87,91,101].…”
Section: Anxiety Depression and Stressmentioning
confidence: 91%
“…En una muestra de 77 pacientes, observaron que a los seis meses del inicio del tratamiento hubo una mejoría en aprendizaje verbal, fluencia verbal y memoria, siendo la recuperación independiente de la edad de los participantes (26) . -Cáncer de pulmón: la anemia derivada de la quimioterapia podría inducir alteraciones en la funcionalidad y rendimiento cognitivo; por lo tanto, el tratamiento de la anemía podría mejorar ambos (27) .…”
Section: Estudios Longitudinalesunclassified
“…No obstante, incluso un deterioro leve puede conllevar consecuencias dramáticas (van Dam et al, 1998), afectando profundamente la vida del paciente, por ejemplo, poniendo en riesgo su desarrollo profesional, obstaculizando la continuación de estudios o el manejo del dinero (Boykoff, Moieni y Karen, 2009). Afortunadamente, para muchos pacientes, se trata de un efecto transitorio, que se resuelve satisfactoriamente con el paso del tiempo (Eberhardt et al, 2006b), sólo un subgrupo de pacientes manifestaría daños prolongados. Según Ahles et al, (2002), las dosis altas provocarían daños persistentes tras 5 años; la quimioterapia afectaría, sobre todo, la memoria verbal y la función psicomotora.…”
Section: Magnitud Del Problemaunclassified